Multicystic renal dysplasia, a histomorphological spectrum: Seven years experience from a tertiary care hospital - Kanika Gupta; Shramana Mandal; Varuna Mallya; Meeta Singh; Nita Khurana; Yogesh K. Sarin (Indian Journal of Pathology and Microbiology)
Objectives: Multicystic dysplastic kidney (MCDK) is defined as the presence of multiple noncommunicating cysts of various sizes, detected sonographically, without evidence of functioning renal parenchyma on dimercaptosuccinic acid renal scan. It has an incidence of 1:4000 live births. They are more commonly diagnosed in boys, usually on the left side, but may also be bilateral. There is the presence of primitive ducts surrounded by fibromuscular connective tissue. These are because of the disturbed connection of the ureteric bud with renal blastema and abnormal division at the stage of metanephros, resulting in an abnormal metanephros differentiation. Materials and Methods: Thirty cases of MCDK were included to study their histomorphology along with their clinical features. Cases were retrieved from the last seven years (2015–2021) from the Department of Pathology, Maulana Azad Medical College. Result: Age ranged from 10 days to 18 years. The cases were between 1 years and 5 years of age. Six out of 30 cases (20%) were infants with three of them being neonates. Twenty-one cases were males. All the cases had unilateral kidney involvement with the left kidney being involved in 20 out of 30 cases. Twenty-eight cases underwent nephrectomy in view of small contracted nonfunctional kidneys with one of them being horseshoe shaped. Five cases had associated hydronephrosis (two ipsilateral and three bilateral). One case had Hirshprung’s disease, four had anorectal malformation, two had posterior urethral valves with vesicourethral reflux, one had duplex moiety, and one had undescended testes. On histopathological examination, all of them showed the presence of immature disorganized tubules surrounded by a collarette of immature mesenchymal stroma. One of the cases showed osteoid formation and four had areas of immature cartilage. Normal kidney parenchyma was seen at the periphery in four cases. Conclusion: This series has been presented to highlight the various histomorphological features of MCDK. MCDK can be managed conservatively in most of cases due to autoinvolution and, hence, needs to be differentiated from other close differentials like polycystic kidney disease, cystic nephroma, and cystic partially differentiated nephroblastoma in order to avoid unnecessary surgical intervention.